PENGARUH PENERAPAN METODE BERCERITA TERHADAP PEMBENTUKAN PERILAKU BAIK PADA ANAK PAUD URIN TUKUNG DESA CEMPAKA BARU - S. Seling, Miliana; Yuniarti, Yuniarti; Diana, Diana (FKIP UM Pontianak, 2026)
This study is motivated by the importance of developing good behavior in early childhood as a foundation for character building. The research problem is how the application of storytelling method affects the formation of good behavior in children aged 5-6 years at PAUD Urin Tukung, Desa Cempaka Baru. The method used was an experimental research design with pre-test and post-test in class B. The results showed that children's good behavior significantly increased after the application of the storytelling method, with the average percentage of children’s behavior rising from 45% in the pre-test to 80.83% in the post-test. Statistical analysis using the t-test indicated that tcount (20.198) > ttable (2.093), proving that the storytelling method is effective in forming good behavior in children. This finding suggests that storytelling can be an enjoyable and effective learning strategy for instilling moral values in early childhood. Future research is recommended to develop variations of the storytelling method and expand the research sample to strengthen the generalizability of the results.